Characterization of Genomic Alterations in Colorectal Liver Metastasis and Their Prognostic Value - Bao, Xuanwen; Wang, Kun; Liu, Ming; Li, Bin; Wang, Hongwei; Jin, Kemin; Yan, Xiaoluan; Zhang, Hangyu; Bao, Quan; Xu, Da; Wang, Lijun; Liu, Wei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Colorectal liver metastases (CRLMs) are clinically heterogeneous lesions with poor prognosis. Genetic alterations play a crucial role in their progression. The traditional Fong clinical risk score (Fong-CRS) is commonly used for risk stratification and prognosis prediction. By identifying the genomic landscape of CRLMs, we aimed to develop a mutation signature-based clinical score (mut-CS) system to improve clinical prognostication. Tumour tissues from 144 patients with CRLMs were analyzed with next-generation sequencing (NGS). A total of 620 genes with somatic mutations and copy number alterations were detected. Clinical data were collected for the patients with CRLMs in our hospital cohort. TP53, APC, KRAS, SMAD, CHEK2, and TCF7L2 were the most significantly altered genes in our CRLM cohort. TCF7L2 alterations were significantly higher in CRLMs originating from the right-side colon than in those originating from the left-side colon. A mut-CS scoring system considering the unique mutation signature, primary site, and Fong-CRS was developed and could identify CRLM patients with poor prognosis. The mean time-dependent receiver operating characteristic curve AUC value of the mut-CS system was greater than that of previously established scoring measures (the Fong-CRS, the e-clinical score, the presence of concomitant RAS and TP53 mutations, and other clinical traits). We identified a mutant signature that exhibits a strong prognostic effect for CRLMs. Traditional clinical scoring system characteristics were incorporated into the new mut-CS scoring system to help determine the appropriate treatment for CRLMs.